Deconstructing psychological therapies as activities in context: What are the goals and what do therapists actually do? - Guerin, Bernard (Perspectivas em Análise do Comportamento, 2017)
Accounts of 19 psychological therapies were analyzed to extract their goals and activities, collated from first- and second-hand accounts and DVDs. Stripped of the theories and all jargon, the diverse-looking therapy systems converged, and the goals and activities could be analyzed into five functional groups: forming a relationship with someone who is a stranger; solving smaller life conflicts in ways which can be done within a clinical setting; the therapist acting as an audience to train new behaviors; sampling the clients’ discourses about their life conflicts; and the therapist acting as an audience to shape these discourses to change the broader life events. These functions were placed in the historical and sociological contexts of therapies arising in the late 1800s, when major life changes began for people in western modernity due to the increases in stranger or contractual social relationships from capitalism and neo-liberalism. For example, much of the therapy process is determined by the (neo-liberal) clinical environment, such as the therapist usually staying within the clinic and engaging clients only for a short time, and dealing with someone who is only in a contractual relationship to the therapist. It was also suggested that these features have probably led to the current emphasis on shaping verbal behaviors (cognitive therapies) through the therapistas-audience. A comparison to the activities within social work showed that there was a large overlap but social work did more outside the contractual relationships and engaged with the clients’ worlds much more.